The Roles of Financial Literacy Level, Social Media, and Religiosity in Takaful Purchase Intention - Ahnaf, Ahnaf; Mardian, Sepky (International Journal of Entrepreneurship and Sustainability Studies, 2025)
The financial literacy and inclusion of Indonesia remain low index, including the takeful awareness. This fact is noteworthy given that Indonesia is a Muslim-majority country and is a highly active user of social media.  This study aims to analyze the influence of Islamic financial literacy, religiosity, and social media on Indonesians’ intention to purchase takeful. Structural Equation Modeling (SEM) was used to analyze the survey data to determine the roles of financial literacy level, social media, and religiosity in takeful purchase intentions. The study involved 149 respondents who intend to purchase takaful products and services in Greater Jakarta, Indonesia. The findings of this study empirically show that the intention to purchase takaful in Indonesia is likely initiated by the level of (islamic) financial literacy. Those who are familiar with takaful products and their benefits are more likely to purchase them. Moreover, the emotional appeal of the market remains a significant factor for Islamic products. Religiosity is a key factor in offering the takeful product to the public, while social media is identified as an effective channel for introducing these products and influencing individual purchasing intentions. This study suggests that the takeful industry and stakeholders must collaborate to intensify efforts to enhance Islamic financial literacy. While religiosity is a crucial element, the industry should also prioritize the value and benefit of takeful products. Furthermore, social media is also an important medium to introduce products and make the public engage with takeful products.